2003
DOI: 10.1557/jmr.2003.0121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of additive and impurity species on the oxide morphology of silicon nitride

Abstract: Si3N4 sintered with Lu2O3 was exposed to 1 atm of oxygen and steam environments at 1200–1400 °C. The effects of additive and impurity species on the morphological development of the oxide layer were examined. Oxide layers grown on as-received samples in oxygen generally contained bubbles and cracks and underwent spallation due to the presence of an initial impurity-laden oxide layer. Oxide layers grown on as-received samples in steam exhibited layered morphology: a glassy outer layer and a cristobalite inner l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Additional details of morphologic development of TGOs on SN282 can be found in a study that we reported elsewhere. 11 The application of a thin mullite coating contributed to marked improvement in the oxidation behavior of SN282. According to Figs.…”
Section: Shown Respectively Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional details of morphologic development of TGOs on SN282 can be found in a study that we reported elsewhere. 11 The application of a thin mullite coating contributed to marked improvement in the oxidation behavior of SN282. According to Figs.…”
Section: Shown Respectively Inmentioning
confidence: 99%
“…Such TGO morphology on steamoxidized SN282 was quite similar to those we reported in a separate study. 11 Further discussions of the morphologic characteristics and development can be found in the reference. It is known that silica recession, due to Si(OH) 4 formation and volatilization, destroys air plasma spray mullite coating in steam.…”
Section: March 2004mentioning
confidence: 99%
“…Si 3 N 4 degradation by oxidation at high temperatures is determined by the grain‐boundary phases, typically based on oxynitride glasses, formed by a combination of the sintering additives with the parent Si 3 N 4 and SiO 2 impurities 1–3 . While oxidizing pure Si 3 N 4 forms a surface film of SiO 2 , the presence of sintering aids (mostly oxides of rare‐earth elements R 2 O 3 ) induces silicate deposits including R 3+ on the surface 1–5 . The intergranular oxynitride glassy phase in Si 3 N 4 provides a continuous transport medium between the surface silicate scale and the Si 3 N 4 bulk, by the outward diffusion of R 3+ cations and inward diffusion of oxygen 1,2 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] While oxidizing pure Si 3 N 4 forms a surface film of SiO 2 , the presence of sintering aids (mostly oxides of rare-earth elements R 2 O 3 ) induces silicate deposits including R 31 on the surface. [1][2][3][4][5] The intergranular oxynitride glassy phase in Si 3 N 4 provides a continuous transport medium between the surface silicate scale and the Si 3 N 4 bulk, by the outward diffusion of R 31 cations and inward diffusion of oxygen. 1,2 While oxidation of Si 3 N 4 -based ceramics in dry air and oxygen was extensively studied, [1][2][3][4][5] it is known that silicon nitride oxidizes up to an order of magnitude faster in wet than in dry oxygen and the mechanism changes from parabolic to paralinear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation